PERJANJIAN SEBAGAI DASAR PENGELOLAAN OBYEK WISATA OLEH DESA ADAT DI KABUPATEN GIANYAR - I Nyoman Punduh (Kerta Dyatmika, 2020)
Abstrak Tourism is one of the mainstays in foreign exchange earnings for national and regional development. For this reason, Indonesia's tourism development must be able to create new innovations to sustain and increase competitiveness in a sustainable manner. At present both at the central and regional levels are regulated according to what is stated in the 1945 Constitution of the Republic of Indonesia Article 18 paragraph (2) states that "Provincial, Regency and City Regional Governments regulate and manage their own government affairs according to the principle of autonomy and co-administration task. â€The granting of broad autonomy to the regions is directed at accelerating the realization of people's welfare through service improvement, empowerment and community participation. Besides that, through broad autonomy, the regions are expected to be able to increase their competitiveness by paying attention to the principles of democracy, equity of justice, special and special characteristics as well as regional potential and diversity in the system of the Unitary State of the Republic of Indonesia. The formulation of the problem in this study is: whether the agreement can be used as the basis of authority by traditional villages in managing tourism objects in Gianyar Regency and whether the obstacles of traditional villages in managing tourism objects in Gianyar Regency. This type of research used in discussing the problem of this study is to use empirical legal research. Empirical law research is research in the form of empirical studies to find theories about the process of occurrence and about the process of working of law in society. The results of the discussion in this study are as follows: Cooperation agreement between the Head of the Gianyar Regency Tourism Office with the Customary Villages and the Tememong Pura which has been in the form of a cooperation agreement between the Head of the Gianyar Regency Tourism Office and the Gunung Kawi Customary Village Tampaksiring Number 9619 / Diparda / 2018, Nomo5 05 / DP-PGK / IV / 2018, this cooperation agreement can be used as the basis of authority by traditional villages in managing tourism objects in Gianyar Regency. Customary villages in managing tourist objects in Gianyar Regency, encountered several obstacles including: Internal barriers, such as Human Resources, management personnel are still low, facilities and infrastructure in tourist objects are still limited, public awareness around the location of objects is still low. External barriers, such as natural disasters such as volcanic eruptions, epidemics such as rabies, bird flu and others and terrorism. Keywords: Customary Village, Tourism, Agreement